Antecedents and Effects of Parasocial Relationships: A Meta-Analysis. (10th November 2020) - Tukachinsky, Riva; Walter, Nathan; Saucier, Camille J
Abstract: The current meta-analysis synthesizes four decades of research (k = 120) on the antecedents and effects of parasocial relationships (PSRs). In line with contemporary theorization of PSRs as an extension of, rather than as a substitution for social relationships, the meta-analysis does not find a significant relationship between social deficiencies and PSRs. PSRs are also strongly correlated with factors that facilitate interpersonal bonds (e.g., homophily), other forms of involvement (e.g., identification, transportation), and persuasive outcomes. Furthermore, the analysis validates the theoretical distinction between PSRs and parasocial interactions (PSIs) revealing only a moderate correlation between the two constructs. Likewise, while PSRs and PSIs did not differ with respect to effects on persuasive outcomes, PSRs emerge as a stronger predictor of media involvement. The findings are discussed in relation to theoretical models of media involvement and effects